ChemInform Abstract: A5RE4X[TO4]4 Crystal Growth: Fluoride Flux Synthesis of Na5Ln4F[GeO4]4 (Ln: Pr, Nd), the First Quaternary Germanate Oxyfluorides. Issue 31 (14th July 2016) - Latshaw, Allison M.; Wilkins, Branford O.; Morrison, Gregory; Smith, Mark D.; zur Loye, Hans‐Conrad
Abstract: Crystals of the title compounds are prepared from mixtures of Ln2 O3 (Ln: Pr, Nd), Na2 CO3, and GeO2 using eutectic NaF/NaCl as flux (Ag crucible, 800 °C, 24 h).